IMPERATIVE DEVELOPMENT OF THE EU DIGITAL ECONOMY IN THE CONTEXT OF GLOBAL TRENDS - IVANTSOV, Serhii (Herald of Khmelnytskyi National University. Economic sciences, 2024)
It is substantiated that the world economy is at the stage of transition to a new long cycle of development. This is accompanied by the formation of a new economic model, which is largely based on the use of new technologies, in particular digital ones. Digital technologies create new opportunities and advantages, become the basis for the digital transformation of various industries and the emergence of new forms of economic organization, which determines the evolution of economic systems. In view of this, the creation of a digital economy will be one of the foundations of the future long cycle. Given that the EU is a leading political and economic player in the world, building a digital economy is of special internal and external importance for it. Therefore, the purpose of the work is to substantiate the imperative of the development of the digital economy of the EU in the context of global trends, which will be the basis for further analysis of strategic guidelines and supranational policy in this area. The main problems and contradictions of the existing economic model are summarized. It is justified that digital technologies create prerequisites for overcoming them. Given the expediency of preserving and improving the existing world order, the role of the EU is important. The challenges facing the EU (existential, civilizational, economic, technological, globally competitive, social, political, transformational) are highlighted, overcoming which the development of the digital economy will help. The need to build such an economy is substantiated from the point of view of a number of structural-technological and socio-economic changes. It was noted that digital transformations have become a prerequisite and driving force for the modernization of the modern economy, which requires the EU to develop a special approach to managing the digital sector as well. The development of the EU's digital economy has a large external aspect, in particular regarding the creation of a global digital order. The geopolitical and geoeconomic significance of building a digital economy for the EU, which requires an independent strategy and purposeful policy in this area, is determined.
Keywords: digital technologies; digital economy; global technological trends; global challenges; world order; socio-economic changes; digital transformations